Prenatal psychological or metabolic stress increases the risk for psychiatric disorders: the "funnel effect" model. (May 2022) - Musillo, Chiara; Berry, Alessandra; Cirulli, Francesca
Abstract: Adverse stressful experiences in utero can redirect fetal brain development, ultimately leading to increased risk for psychiatric disorders. Obesity during pregnancy can have similar effects as maternal stress, affecting mental health in the offspring. In order to explain how similar outcomes may originate from different prenatal conditions, we propose a "funnel effect" model whereby maternal psychological or metabolic stress triggers the same evolutionarily conserved response pathways, increasing vulnerability for psychopathology. In this context, the placenta, which is the main mother-fetus interface, appears to facilitate such convergence, re-directing "stress" signals to the fetus. Characterizing converging pathways activated by different adverse environmental conditions is fundamental to assess the emergence of risk signatures of major psychiatric disorders, which might enable preventive measures in risk populations, and open up new diagnostics, and potentially therapeutic approaches for disease prevention and health promotion already during pregnancy. Graphical Abstract: ga1 Highlights: Different challenges in utero have similar negative effects on fetal brain. Maternal obesity is a stressor for both the mother and the fetus. Psychophysical and metabolic stress converge on shared stress-sensitive pathways. The placenta acts as a "funnel" conveying different stressors to the fetus. Inflammation, glucocorticoids and metabolic markers mediate the effects of stress.